Avaliação do modelo de transtorno de estresse póstraumático (TEPT) e camundongos machos : efeitos do midazolam, sertralina e ausência de efeito da imipramina - Costa, Fernando de Souza Melo (2008)
The post-traumatic stress disorder (PTSD) affects a portion of subjects exposed to a traumatic event. This disorder leads to long-term alterations in the hypothalamus-pituitaryadrenal (HPA) axis, autonomic and cognitive function. The aim of our study was to evaluate whether the animal model of PTSD proposed for rats could be used in mice and, to evaluate the effect of benzodiazepine, tricycle antidepressant and selective serotonin reuptake inhibitor drugs in the PTSD model. For this we realized the following experiments: Experiment 1- The test consisted of exposure the male mice to inescapable electric footshock (0.3 mA) in the black side (BS) of the black-white box (BW). In the 7th, 14th and 21th day, mice were reexposed to the traumatic reminder on the white side (WS) or BS for 2 min, without footshock. In the 29th day, the animals were submitted to elevated plus-maze (EPM) for record the anxiety indexes [percentage of open arm entries (%OA) and percentage of open arm time (%OT) and as well as general locomotor activity, closed arm entries (CE)]. On day 34 the same animals were submitted to BW test for record the latency to escape (LE) from WS and time spent on WS of the BW box. Experiment 2 the same procedure of experiment 1 was performed, except that the animals were re-exposed at 7th, 14th e 21th days to reminder situation only in WS of BW box for 2 min, without footshock. On day 29th, the animals were exposed to EPM, 30 min after receiving treatment with midazolam. In 34th day the same animals after receiving treatment with midazolam were submitted to BW box test. Experiment 3, 4 and 5 - the same procedure was adopted from experiment 2, except that in 29th day, the animals were not submitted to EPM test and on 34th day 30 minutes after treatment with midazolam, imipramine and sertraline were submitted to BW box. Two-way ANOVA (stimulus x place remainder or treatment) followed by Duncan test showed that PTSD model increased anxiety in mice (P<0.05). The re-exposure in BS promoted anxiogenic-like effect extinction of the model. The midazolam treatment (1.0 and 2.0 mg/kg, i.p.) produced anxiolytic-like effect in maze-mice (P < 0.05) and the 0.5 mg/kg decreased latency to escape of WS (P < 0.05) of BW box and increased the exploratory activity, suggesting involvement of this GABA-benzodiazepine agonist on this PTSD modulation. The EPM test does not interfere in the evaluation of the BW test. It is important to note that no other behaviors were significantly altered by imipramine per se (P < 0.05). The sertraline (5.0 mg/kg), selective serotonin reuptake inhibitor, produced anxiolytic-like effect in the BW test (P < 0.05) and increase exploration activity. These results suggest that the employed PTSD model to study neurobiological disturbances associated with this disorder.